Chapter 9 Best Practice Guidance for Political Staffing for Political Managers, Advisers, and Reformers - Lees-Marshment, Jennifer (Taylor & Francis, 2024)
This chapter sets out an overall vision and architecture for political staffing and why it is needed. It discusses the privilege of service in political staffing, notes the current crisis in political staffing human resource management but also argues strongly for the potential for positive human resource management. It provides guidance for practitioners by outlining best practice guidance for political staffers, their managers, and reformers. This makes clear the key approaches and tools they need to be aware of and use to improve political offices. Political staffers and advisers need to be properly trained, supported and developed. Not only will this benefit the individuals in the roles, it will provide significant benefit to the politicians they work for and in turn the voters who elect the politicians. Higher quality human resource management for political staffers and advisers will generate multiple long term dividends. It will create higher calibre, more experienced and diverse political staffers who are up and running in their role sooner, perform at a higher level and are retained for longer, preserving institutional knowledge. This will lead to higher functioning offers, generating better outputs, more effectively supported politicians, more strategic decisions, increased delivery of election promises.